Weight loss practices, perceptions, and eating disorder symptoms among Chinese male adolescent combat sports athletes - Meng, F.; Zhang, Z.; Xu, K.; Lvu, M.; Zhong, Y. (Frontiers in Nutrition, 2026)
Objectives: This study investigated weight loss (WL) practices, perceptions, and eating disorder (ED) symptoms among Chinese male adolescent combat sport (CS) athletes.